2002
DOI: 10.1097/00005344-200202000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Inhibits Serum-Depletion-Induced Apoptosis of Human Vascular Endothelial Cells by Inducing Nitric Oxide via Calcium Ion Kinetics

Abstract: Vascular endothelial cells play important roles in atherogenesis, and bradykinin is associated with atherosclerosis. The effect of bradykinin on apoptosis in human umbilical vein endothelial cells (HUVECs) was investigated, with a focus on Ca2+ kinetics and nitric oxide production. In serum-free conditions, the number of apoptotic cells increased in a time-dependent manner, but this increase was inhibited by bradykinin in a dose-dependent manner. The apoptosis inhibited by bradykinin was reduced by nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In addition to various other biological effects, BK has been shown to protect ECs against apoptotic cell death in vitro (Fujita et al, 2000;Gryglewski et al, 2001;Kono et al, 2002;Ceconi et al, 2007). More recently, Oeseburg et al (2009) used cultured bovine aortic EC to show that BK may also protect ECs against oxidative stress-induced senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to various other biological effects, BK has been shown to protect ECs against apoptotic cell death in vitro (Fujita et al, 2000;Gryglewski et al, 2001;Kono et al, 2002;Ceconi et al, 2007). More recently, Oeseburg et al (2009) used cultured bovine aortic EC to show that BK may also protect ECs against oxidative stress-induced senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of the in vitro functional studies that have demonstrated real EC protection against noxious stimuli by BK, either added or endogenously produced via ACEi and ARA treatments, were conducted on macrovascular ECs from conductance vessels such as the bovine aorta (Gryglewski et al, 2001), the human umbilical vein (HUVEC) (Kono et al, 2002;Ceconi et al, 2007), and the human aorta (HAEC) (Fujita et al, 2000). There is no doubt about functional phenotypic heterogeneity of ECs between macro-and microvessels.…”
mentioning
confidence: 99%
“…To answer this question, we have measured the balance between Ang II and BK, as they are modulated by ACE and exert pro-apoptotic and anti-apoptotic effects on the endothelium, respectively [25,26]. An increase in BK levels is also expected to stimulate eNOS protein expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on BK as modulator of apoptosis are very few. In vitro, BK has been reported to inhibit serum-depletion-induced apoptosis of endothelial cells by increased NO production [15]. In the heart, BK is considered as a cardioprotective agent which prevents apoptosis [16] possibly via an NO pathway.…”
Section: Discussionmentioning
confidence: 99%